Microwave-Assisted Synthesis of Nonsymmetrical Aryl Ethers Using Nitroarenes - Sarkate, Aniket P.; Bahekar, Sushilkumar S.; Wadhai, Vijay M.; Ghandge, Ganesh N.; Wakte, Pravin S.; Shinde, Devanand B. (Synlett, 2013)
An efficient, microwave-assisted ligand-free, catalyst-free synthetic method for nonsymmetrical diaryl ethers has been developed by using nitroarenes. A variety of phenols and nitroarenes was scanned by using this method to produce nonsymmetrical aryl ethers. The newly developed method is an ecofriendly and cost-effective approach to synthesize nonsymmetrical aryl ethers.
Keywords: microwave; ligand-free; catalyst-free; nonsymmetrical diaryl ethers; O-arylation